PENDIDIKAN KARAKTER RELIGIUS, DISIPLIN DAN BAKAT MELALUI PENIGKATKAN KUALITAS SARANA PRASARANA SEKOLAH - Kautsar, Andri; Edi, Johan (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2017)
This research focused on the character education program, and its function in instilling character education through Infrastructure. This research was qualitative. Data collection techniques used in this research were observation, in-depth interviews, documentation studies and literature studies. The results revealed that the change happened after the implementation of Infrastructure related to shaping the quality and character of the learners; after the establishment of mosque facilities, the students were familiar with prayer jamaah, read the Quran with Islamic poetry, could be da'i and daiyah islam, understanding hadith, tafsir al-Qur'an, able to write calligraphy and able to make scientific work of Islam. Changes that occurred after the Infrastructure materialized was the learners more religious, talented and disciplined.